Tipologías actuales de asesinos sexuales seriales (2017)
In this monographic work three typologies of sexual murderers were examined through the empirical evidence that supports them. A systematized search of the empirical studies available on the different classifications was carried out, and the methodology, results and limitations of the same were evaluated. It was found that there is a significant shortage of studies that support the classifications on which criminal profiling is based, which calls into question their validity and reliability. More research is needed to demonstrate the functionality and validity of the typologies, considering that, at the moment, many investigators consider them as an important tool in the detection of a serial killer.